Aerosol Optical Density of Atmosphere And Possibility of Its Definitions By Means of Integrated Radiation of the Sun - Tavartkiladze, Kukuri A. (Journals of Georgian Geophysical Society, 2017)
It is considered the possibility of determination of atmosphere optical density to the integral solar radiation. The respective integral equation kernel together with the spectral solar constant consist the functions of penetration of the molecular dissipation of the water vapor and ozone. These penetration functions are obtained and from the integral equation was found the aerosol optical density of atmosphere. Obtained solution was used for study of the aerosol optical density distribution above the territory of Georgia.